Gender Friendly Approach in Curriculum Transaction: Some Issues and Guidelines in Arunachal Pradesh. - Baral, G.C. (THE PRIMARY TEACHER, 2008)
Education of the girl child, especially of the tribal girls in our country has been a major challenge so far. The reasons for the relative educational deprivation of the girls may, depend upon different situations. In a tribal society where gender role, stereotypes are perceived to be natural and are perpetuated from generation to generation; amount of incentives to the girls in the form of free tuition, free textbooks, free school uniforms and free hostel facility etc. is considered to be adequate enough for increasing their participation but, in such situations, a gender friendly approach in curriculum transaction on the part of a teacher is an important means for giving equal treatment to both the boys and girls at every level of curriculum transaction in the school. This paper aims at sensitising the primary level teachers about the need and importance of a gender friendly approach in curriculum transaction in both scholastic and coscholastic areas of school education in the tribal socio-cultural context of Arunachal Pradesh.